2018
DOI: 10.3389/fnmol.2018.00230
|View full text |Cite
|
Sign up to set email alerts
|

The F238L Point Mutation in the Cannabinoid Type 1 Receptor Enhances Basal Endocytosis via Lipid Rafts

Abstract: Defining functional domains and amino acid residues in G protein coupled receptors (GPCRs) represent an important way to improve rational drug design for this major class of drug targets. The cannabinoid type 1 (CB1) receptor is one of the most abundant GPCRs in the central nervous system and is involved in many physiological and pathophysiological processes. Interestingly, cannabinoid type 1 receptor with a phenylalanine 238 to leucine mutation (CB1F238L) has been already linked to a number of both in vitro a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…In cultured hippocampal neurons, CB1R has a wide intracellular distribution but its plasma membrane surface expression is highly polarized toward the axonal compartment (Figure 1; Irving et al, 2000;Coutts et al, 2001;Leterrier et al, 2006;McDonald et al, 2007a;Fletcher-Jones et al, 2019). CB1R displays a disto-proximal gradient of CB1R expression along the entire axonal plasma membrane (Simon et al, 2013;Wickert et al, 2018) with fine axons reported to exhibit highly punctate surface labeling, often co-localized with sites of synaptic contact (Irving et al, 2000;Coutts et al, 2001). Immunogold electron microscopy analysis of rat brain sections (Katona et al, 1999;Nyiri et al, 2005) and STORM super-resolution imaging (Dudok et al, 2015) detect CB1R predominantly at the presynaptic terminal, concentrated in the plasma membrane at axonal perisynaptic regions of both GABAergic and glutamatergic neurons (Katona et al, 1999(Katona et al, , 2006Kawamura et al, 2006).…”
Section: Cannabinoid Receptor 1 (Cb1r)mentioning
confidence: 99%
See 2 more Smart Citations
“…In cultured hippocampal neurons, CB1R has a wide intracellular distribution but its plasma membrane surface expression is highly polarized toward the axonal compartment (Figure 1; Irving et al, 2000;Coutts et al, 2001;Leterrier et al, 2006;McDonald et al, 2007a;Fletcher-Jones et al, 2019). CB1R displays a disto-proximal gradient of CB1R expression along the entire axonal plasma membrane (Simon et al, 2013;Wickert et al, 2018) with fine axons reported to exhibit highly punctate surface labeling, often co-localized with sites of synaptic contact (Irving et al, 2000;Coutts et al, 2001). Immunogold electron microscopy analysis of rat brain sections (Katona et al, 1999;Nyiri et al, 2005) and STORM super-resolution imaging (Dudok et al, 2015) detect CB1R predominantly at the presynaptic terminal, concentrated in the plasma membrane at axonal perisynaptic regions of both GABAergic and glutamatergic neurons (Katona et al, 1999(Katona et al, , 2006Kawamura et al, 2006).…”
Section: Cannabinoid Receptor 1 (Cb1r)mentioning
confidence: 99%
“…Lipid rafts are specialized microdomains of plasma membrane rich in sphingolipids and cholesterol (Allen et al, 2007) and plasma membrane expressed CB1R has been reported to reside in lipid rafts (Sarnataro et al, 2005;Asimaki and Mangoura, 2011). Indeed, membrane cholesterol depletion using methyl-β-cyclodextrin (MβCD), which disrupts lipid rafts, is an effective way of preventing CB1R endocytosis (Keren and Sarne, 2003;Leterrier et al, 2004Leterrier et al, , 2006) and a mutation that increases lipid raft association of CB1R (CB1R-F238L) increases constitutive endocytosis of CB1R (Wickert et al, 2018). Association with lipid raft domains has also been proposed to influence receptor signaling and ligand binding (Keren and Sarne, 2003;Bari et al, 2005Bari et al, , 2008Wu et al, 2008) and this association has been reported to rely on palmitoylation of cysteine residue C416 in rat CB1R (see "Palmitoylation of ctCB1R" section below).…”
Section: Mechanisms Of Agonist-induced Endocytosismentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings with imaging probes likely reflect the dynamics of CB 1 in neurons as both probes in live neurons displayed a spatial pattern similar to that of CB 1 antibody in fixed neurons. Previous studies have shown that GPCRs form homodimers, heterodimers, or oligomers to affect their downstream signaling pathways [23][24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings with imaging probes likely reflect the dynamics of CB 1 in neurons as both probes in live neurons displayed a spatial pattern similar to that of CB 1 antibody in fixed neurons. Previous studies have shown that GPCRs form homodimers, heterodimers, or oligomers to affect their downstream signaling pathways 28,29,30,31 .…”
Section: Discussionmentioning
confidence: 99%